Creativity in Utilizing Waste into Functional Products as the College Students’ Concern toward the Environment - Titin Titin; Eko Sri Wahyuni; Elsa Ferella (Indonesian Journal of Biology Education, 2022)
This research presents the creativity of the college students of Biology Education Study Program of Universitas Tanjungpura in processing and utilizing both the organic and inorganic waste into several functional products. The type of this research is qualitative research with a descriptive approach to describe the types of useful products from waste made by the college students of Biology Education Study Program. The product assessment is carried out by 3 validators, who are 2 lecturers at IKIP PGRI Pontianak and 1 lecturer at the Faculty of Education and teachers training (FKIP) of Universitas Tanjungpura. The creativity of the college students in utilizing waste into functional products produces several products in the form of foods and crafts. Moreover, the food products include Empek-empek mackerel fish bones, chicken intestine nuggets, avocado seed cookies, watermelon skin sweetmeat, jackfruit seed chips, and fluffy mini pancake banana peel. Then, the handicraft products include piggy banks made from used bottles, bags made of jerry cans and patchwork, miniature of trees with lights and electrical terminals made from old newspapers and old tires, and the bracelet friendship summer. Finally, the validator's assessment of the food products is in the range of 2 - 5, while for the handicraft products is in the range of 2 - 4.5.